Chromatosim 2 : a user-friendly general rate chromatography simulator - Nilam, Ricky. (2010)
With the purpose of simulating chromatography, this project attempted to numerically solve via MATLAB the PDE model equations of fluid convection flow involving dispersion and adsorption. For this reason, a systematic interface was developed for easy application. The project started with the simplest model such as liquid chromatography assuming linear isotherm to begin with. Two different approaches are applied: Equilibrium-Dispersive and General Rate model. There are as well two method of solving PDE: Finite Difference Method (FDM) and Lattice Boltzmann method (LBM). FDM approximation proves to be stable for wide range of parameters with rationally acceptable deviation compared to the ideal case. On the other hand, LBM method is able to produce similar result but much faster than FDM, though the range of parameters should be considered to be within stability limit. Since the result satisfied the analytical solution, the simulation was expanded to include more complex cases such as multi component chromatography and competitive Langmuir isotherms. The interface itself has been built with useful features and able to accept user defined isotherm.